Experience in the use of collagen phytoplates in the treatment of gingivitis - Sultan Kozhemov, Inna Pustokhina, Svetlana Danshina, Anton Timoshin, Andrey Sevbitov, Elena Ergesheva, Sergey Mironov, (Opción, 2019)
According to the WHO, various forms of gingivitis account for more than 60% of all inflammatory periodontal diseases. Gingivitis is an initial inflammatory disease of periodontal tissues and may result in a severer disease – periodontitis – if not treated in a timely fashion. In its turn, periodontitis is a severer disease, which is as hard to treat as gingivitis. Furthermore, treatment may not result in a desired outcome. Therefore, gingivitis treatment is an urgent issue of practical dentistry. The aim of this study was to compare performance of different gingivitis medicines. Methods: We studied the local inflammatory conditions within the periodontium as a response to the Holysal gel on the basis of the clinical data relating to the oral cavity, and compared the gingival inflammation therapeutic effect of the above gel with the product developed at the Sechenov Research Center of the Moscow Medical Academy – Farmadont. Results: The use of Farmadont resulted in a significantly reduced duration of gingivitis treatment. Conclusions: The use of Farmadont collagen phytoplates improves the efficient local treatment and prevention of gingivitis.